2016
DOI: 10.1021/acs.analchem.6b01574
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Bisphenol-A Electrochemical Aptasensor Based on Poly(Pyrrole-Nitrilotriacetic Acid)-Aptamer Film

Abstract: An electrochemical highly sensitive aptasensor was developed based on electropolymerized poly(pyrrole-nitrilotriacetic) acid film and a new aptamer functionalized by a pentahistidine peptide for the quantification of bisphenol A. A surface coverage of antibisphenol A aptamer of 1.84 × 10(-10) mol cm(-2) was estimated from the electrochemical signal of the [Ru(III)(NH3)6](3+) complex bound by electrostatic interactions onto the aptamer-modified electrode. The binding of bisphenol A onto the polymer film was suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…7). 78 A strongly sensitive electrochemical aptasensor based on electropolymerized poly(pyrrolenitrilotriacetic) acid lm and a novel aptamer functionalized with a penta-histidine peptide to quantify bisphenol A was designed by Kazane et al 79 The electrochemical signal of the [RuIII(NH 3 ) 6 ] 3+ complex bound by the electrostatic interaction over the aptamer-modied electrode was used to estimate the surface coverage of the antibisphenol A aptamer of 1.84 Â 10 À10 mol cm À2 . The binding of bisphenol A over the polymer lm has been substantially described by the electrochemical techniques of SWV and EIS measurements.…”
Section: Electrochemical Sensingmentioning
confidence: 99%
“…7). 78 A strongly sensitive electrochemical aptasensor based on electropolymerized poly(pyrrolenitrilotriacetic) acid lm and a novel aptamer functionalized with a penta-histidine peptide to quantify bisphenol A was designed by Kazane et al 79 The electrochemical signal of the [RuIII(NH 3 ) 6 ] 3+ complex bound by the electrostatic interaction over the aptamer-modied electrode was used to estimate the surface coverage of the antibisphenol A aptamer of 1.84 Â 10 À10 mol cm À2 . The binding of bisphenol A over the polymer lm has been substantially described by the electrochemical techniques of SWV and EIS measurements.…”
Section: Electrochemical Sensingmentioning
confidence: 99%
“…Till now, BPA has been widely employed as a monomer to synthesize polycarbonate, expoxy resin, polysulfone resin and other various polymer materials [2]. These polymer materials are mostly used to produce storage containers, nursing bottles, thermal papers, medical apparatus, food can linings and supply pipes [3]. However, toxicology studies have shown that BPA is a typical endocrine-disrupting compound (EDC) in which even a low level can mimic and interfere with hormonal activity by interfering with growth and reproductive development [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a second electrosynthesis could be done, using for example functionalized monomer in order to prepare a biosensor [40][41][42][43][44][45][46], or using organic solvent containing anions which could be drugs [47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%